Inhibitory Effects of Bovine Lactoferricin-Lactoferrampin on Senecavirus A and Foot-and-Mouth Disease Virus with Recombinant Lactobacillus Oral Treatment in Mice - Wenyue Zhao; Senhao Zhang; Ling Sui; Xiaona Wang; Jiaxuan Li; Wen Cui; Yanping Jiang; Xinyuan Qiao; Lijie Tang (Veterinary Sciences)
Foot-and-mouth disease virus (FMDV) and Senecavirus A (SVA) have similar pathogenic characteristics, and both are important pathogens that harm the livestock industry. Studies have shown that lactoferrin peptides can inhibit the replication of various viruses and enhance the body’s immune functions. Based on this, in the present study, we aimed to investigate the effects of bovine lactoferricin-lactoferrampin (LFCA) on replicating FMDV and SVA and to analyze its role in the cellular antioxidant response caused by viral infection; in addition, we fed mice with constructed recombinant Lactobacillus reuteri expressing LFCA. Treatment with LFCA at different stages significantly inhibited the replication of both SVA and FMDV. Pretreatment before SVA infection achieved an inhibition rate of up to 94.9%, while treatment during the FMDV replication stage achieved an inhibition rate of 74.3%. After infection with either virus, intracellular ROS and MDA levels were significantly reduced, as was GSH-Px activity. However, SOD activity showed no significant difference, compared with the virus-exposed group, and remained at a high level, suggesting an increased cellular antioxidant capacity. LFCA treatment significantly increased the transcription levels of the Nrf2, Ho-1, and Nqo1 genes. In mouse experiments, the LFCA-treated group showed significantly lower viral loads in lung and intestinal tissues, compared with the SVA infection group, validating LFCA’s protective effect against SVA infection. These findings demonstrate the potential of LFCA as an antiviral drug.